if x=2+2^(2/3)+2^(1/3)

then x^3-6x^2+6x= ?
Please show the steps

3 years ago

Share

Answers : (2)

                                        

dear Raunak,


the answer to your question is 2


we have x-2=22/3-21/3


then cubing both sides to get,


(x-2)3= 6(x-2)


thus expnding to get,


x3-6x2+6x=2



BEST OF LUCK

Please approve the answer...!!!!!!
We are all IITians and here to help you in your IIT JEE preparation.
Now you can win exciting gifts by answering the questions on Discussion Forum. So help discuss any query on askiitians forum and become an Elite Expert League askiitian.
Now you score 5+15 POINTS by uploading your Pic and Downloading the Askiitians Toolbar : Click here to download the toolbar..  
AMAN BANSAL

3 years ago
                                        

dear raunak,


I have already posted reply to your question.



BEST OF LUCK

Please approve the answer...!!!!!!
We are all IITians and here to help you in your IIT JEE preparation.
Now you can win exciting gifts by answering the questions on Discussion Forum. So help discuss any query on askiitians forum and become an Elite Expert League askiitian.
Now you score 5+15 POINTS by uploading your Pic and Downloading the Askiitians Toolbar : Click here to download the toolbar..  
AMAN BANSAL

3 years ago

Post Your Answer

More Questions On Algebra

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
Given: [a/(b+c)] + [b(a+c)] + [c/(a+b)] = 1 Then What is the Value of : [a 2 /(b+c)] + [b 2 (a+c)] + [c 2 /(a+b)] ?
 
 
Hello student, Please find the response to your question below I think there is some data missing or some mistake in your question. whether it is b(a+c) or b/a+c also it is b 2 (a+c) or b 2...
  img
SHAIK AASIF AHAMED 2 months ago
 
We have (a+b+c)[ (a/b+c) + (b/c+a) + (c/a+b) ] = a^2/(b+c)+b^2/(c+a)+c^2/(a+b) + (a+b+c) Hence if (a/b+c) + (b/c+a) + (c/a+b) =1, the equation becomes a+b+c = a^2/(b+c)+b^2/(c+a)+c^2/(a+b) +...
 
mycroft holmes 2 months ago
 
Sir, Thankyou for the response so that i could post the accurate question as follows: [a/(b+c)] + [b / (a+c)] + [c/(a+b)] = 1 Then What is the Value of : [a 2 /(b+c)] + [b 2 / (a+c)] + [c 2...
 
Hari Eeshwar 2 months ago
Let a,b,c E R and a (is not equal to 0) be such that (a+c) 2 2, then the quadratic equation ax 2 + bx + c = 0 has : Imaginary roots. Real roots. Exactly one real root lying in the...
 
 
Hello student, Please find my response to your question below Iam unable to interpret your query Because you didot mention the condition clearly here so without condition you may not get an...
  img
SHAIK AASIF AHAMED 2 months ago
 
Hello student, Please find my response to your question below What does the line’a (is not equal to 0) be such that (a+c) 2 ’mean it does not have a meaning i think there should...
  img
SHAIK AASIF AHAMED 2 months ago
 
in the first line it is (a+c)^2
 
Ujjwal 2 months ago
If p,q are the roots of the quadratic equation x 2 -10rx-11s=0 and r,s are roots of x 2 -10px-11q=0,then find the value of p+q+r+s.
 
 
Hello student, Please find the answer to your question below Givenx 2 -10rx-11s=0........(1) x 2 -10px-11q=0....(2) As p is a root of 1 we get p 2 -10pr-11s=0 and r is a root of 2 so r 2...
  img
SHAIK AASIF AHAMED one month ago
 
p, q are the roots of the quadratic equation x 2 - 10rx – 11s = 0 . r, s are the roots of the quadratic equation x 2 – 10px – 11q = 0. The two equations are perfectly symmetric with roots...
 
Satyajit Samal one month ago
 
1210
 
PRAMAY one month ago
Q . THE AREA ENCLOSED BETWEEN THE CURVES - y = ln ( x + e ) and x = ln ( 1/y ) AND X-AXIS.
 
 
Ans: Hello Student, Please find answer to your question below Intersect x-axis at (1-e, 0) & y-axis at (0, 1) Intersect y-axis at (0, 1). Area A b/w two curves is:
  img
Jitender Singh yesterday
 
thanks sir......and happy diwali.......
 
bharat makkar yesterday
Let f : A-> A where A = { 1, 2, 3, 4, 5} such that ff(x) = x . How many such functions are possible
 
 
First note that the function is injective: f(x) = f(y) implies f(f(x)) = f(f(y)) which yields x = y. We say that a number x is fixed by f if f(x) = x. Now, if f(a) = b, with a and b unequal,...
 
mycroft holmes one month ago
 
In general the real functions which satisfies the condition that fof(x) = x are (i) f(x) = a – x where a is any real no. (ii) f(x) = x But here, f: A → A is the function which should satisfy...
 
Y RAJYALAKSHMI one month ago
 
Pl. ignore this solution – it is incomplete
 
Y RAJYALAKSHMI one month ago
Suppose x 1 & x 2 are the point of maximum and the point of minimum respectively of the function f(x) = 2x 3 – 9ax 2 + 12a 2 x + 1 respectively, then for the equally x 2 1 = x 2 to be true...
 
 
The extreme points are attained at f ’(x) = 0 => 6x 2 – 18ax + 12a 2 = 0 => x = 2a, a f ’’(x) = 12x – 18a f ’’(x) 0 if x = 2a Hence the min at x = 2a = x 1 & max at x = a = x 2 The condition...
 
Y RAJYALAKSHMI 2 months ago
View all Questions »